2020
DOI: 10.3168/jds.2019-17383
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of calf mortality in Great Britain

Abstract: National bodies in Great Britain (GB) have expressed concern over young stock health and welfare and identified calf survival as a priority; however, no national data have been available to quantify mortality rates. The aim of this study was to quantify the temporal incidence rate, distributional features, and factors affecting variation in mortality rates in calves in GB since 2011. The purpose was to provide information to national stakeholder groups to inform resource allocation both for knowledge exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 33 publications
2
42
2
1
Order By: Relevance
“…The herd sizes observed in this study were typically smaller than those reported in the US and other parts of the UK [11,15] but larger than those surveyed in Europe [17,28]. Several studies have associated larger herd sizes with increased calf mortality [28,29]; however, Murray et al [30] found conflicting evidence.…”
Section: Farm Demographicscontrasting
confidence: 52%
See 2 more Smart Citations
“…The herd sizes observed in this study were typically smaller than those reported in the US and other parts of the UK [11,15] but larger than those surveyed in Europe [17,28]. Several studies have associated larger herd sizes with increased calf mortality [28,29]; however, Murray et al [30] found conflicting evidence.…”
Section: Farm Demographicscontrasting
confidence: 52%
“…As the dairy heifer accumulates cost throughout the rearing period until first calving, this represents a significant economic loss to farmers. More recently, Hyde et al [11] found mortality in dairy calves in the UK to be 6% in the first 3 months of life and that changes in mortality were minimal when compared with the 1990s [12]. Improvements to calf health and performance with developments in nutrition and healthcare may be limited by a poor environment, and similarly poor nutrition and healthcare may negate the effects of a good environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, these observations are supported by many of the other studies that either did not report exact numbers over time or that presented data over a shorter period of time. Findings reported by authors included those where the largest proportion of deaths in cattle occurred intrapartum ( Mock et al ., 2020 ), in the first 48 hours ( Busato et al ., 1997 ; Raboisson et al ., 2013 ), the first week ( Gardner et al ., 1990 ), first one- ( Menzies et al ., 1996 ), two- ( Santman-Berends et al ., 2019 ), or three- ( Hyde et al ., 2020 ) months of life.…”
Section: Resultsmentioning
confidence: 99%
“…This could give an overly optimistic representation of calf production on the selected farms by being based on the best calves. Reasons for decreasing numbers of calves weighed with increasing age are unknown; however, calf mortality as a contributory factor (Brickell and Wathes, 2011;Hyde et al, 2020) should be considered before developing calf management strategies based on weight measurements alone.…”
mentioning
confidence: 99%